Case Series: Fractional Anisotropy Along the Trajectory of Selected White Matter Tracts in Adolescents Born Preterm With Ventricular Dilation. (June 2013) - Myall, Nathaniel J.; Yeom, Kristen W.; Yeatman, Jason D.; Gaman-Bean, Shayna; Feldman, Heidi M.
This case series assesses white matter microstructure in 3 adolescents born preterm with nonshunted ventricular dilation secondary to intraventricular hemorrhage. Subjects (ages 12-17 years, gestational age 26-29 weeks, birth weight 825-1624 g) were compared to 3 full-term controls (13-17 years, 39-40 weeks, 3147-3345 g) and 3 adolescents born preterm without ventricular dilation (10-13 years, 26-29 weeks, 630-1673 g). Tractography using a 2 region of interest method reconstructed the following white matter tracts: superior longitudinal/arcuate fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, uncinate fasciculus, and corticospinal tract. Subjects showed increased fractional anisotropy and changes in the pattern of fractional anisotropy along the trajectory of tracts adjacent to the lateral ventricles. Tensor shape at areas of increased fractional anisotropy demonstrated increased linear anisotropy at the expense of planar and spherical anisotropy. These findings suggest increased axonal packing density and straightening of fibers secondary to ventricular enlargement.